1993
DOI: 10.1159/000288679
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Aspects of Neural-Immune Signaling

Abstract: Noradrenergic and peptidergic nerve fibers abundantly innervate the parenchyma of both primary (bone marrow) and secondary (spleen, lymph nodes) lymphoid organs. Nerve fibers distribute within the parenchyma of these organs, as well as along smooth muscle compartments. Both noradrenaline and peptides such as substance P have been shown to fulfill the basic criteria for neurotransmission with lymphocytes, macrophages, and other immunocytes as targets. Denervation or pharmacological manipulation of these neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…While a number of studies indicate that catecholamines participate in cytokine production [1,2,3,4,5,6,7,8,9,10,11,12], we found no evidence of a quantitative link between the degree of sympathetic nervous activation and the magnitude of the inflammatory response during a period of 10 days after SAH.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…While a number of studies indicate that catecholamines participate in cytokine production [1,2,3,4,5,6,7,8,9,10,11,12], we found no evidence of a quantitative link between the degree of sympathetic nervous activation and the magnitude of the inflammatory response during a period of 10 days after SAH.…”
Section: Discussioncontrasting
confidence: 96%
“…Emerging evidence indicates that the sympathetic nervous system, through its innervation of lymphoid organs, can modulate the inflammatory response [1,2,3,4,5,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical studies show that there is the innervation of both primary and secondary lymphoid organs with sympathetic nerve fibers (10,11,(37)(38)(39), and that mast cells are also often found in the proximity of nerve fibers containing neuropeptides in a variety of tissues including skin, intestine, and dura mater (34,(40)(41)(42). Based on electron microscopic observation, nerve terminals are in direct apposition to T cells and mast cells.…”
Section: Coculture Systemmentioning
confidence: 99%
“…Sympathetic nerve fibers innervate the vasculature and parenchyma of primary and secondary lymphoid organs, and other lymphoid tissues (10,11). Immunohistochemical studies demonstrated a close association of sympathetic nerve terminals with macrophages and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%